Online fluorescence spectroscopy for the real-time evaluation of the microbial quality of drinking water. (15th June 2018) - Sorensen, J.P.R.; Vivanco, A.; Ascott, M.J.; Gooddy, D.C.; Lapworth, D.J.; Read, D.S.; Rushworth, C.M.; Bucknall, J.; Herbert, K.; Karapanos, I.; Gumm, L.P.; Taylor, R.G.
Abstract: We assessed the utility of online fluorescence spectroscopy for the real-time evaluation of the microbial quality of untreated drinking water. Online fluorimeters were installed on the raw water intake at four groundwater-derived UK public water supplies alongside existing turbidity sensors that are used to forewarn of the presence of microbial contamination in the water industry. The fluorimeters targeted fluorescent dissolved organic matter (DOM) peaks at excitation/emission wavelengths of 280/365 nm (tryptophan-like fluorescence, TLF) and 280/450 nm (humic-like fluorescence, HLF). Discrete samples were collected for Escherichia coli, total bacterial cell counts by flow cytometry, and laboratory-based fluorescence and absorbance. Both TLF and HLF were strongly correlated with E. coli (ρ = 0.71–0.77) and total bacterial cell concentrations (ρ = 0.73–0.76), whereas the correlations between turbidity and E. coli (ρ = 0.48) and total bacterial cell counts (ρ = 0.40) were much weaker. No clear TLF peak was observed at the sites and all apparent TLF was considered to be optical bleed-through from the neighbouring HLF peak. Therefore, a HLF fluorimeter alone would be sufficient to evaluate the microbial water quality at these sources. Fluorescent DOM was also influenced by site operations such as pump start-up and the precipitation of cations on the sensor windows. Online fluorescent DOM sensors are a better indicator of the microbial quality of untreated drinking water than turbidity and they have wide-ranging potential applications within the water industry. Graphical abstract: Highlights: First use of online fluorescence spectroscopy for assessing microbial water quality. Fluorescent dissolved organic matter (DOM) is strongly correlated with E. coli . Fluorescent DOM is strongly correlated with total bacterial cell counts. Fluorescent DOM is a superior indicator than turbidity of microbial water quality.